Giant bullous emphysema. Surgical treatment: pathophysiology and indications - Villegas, Alejandro H; Viola, Angel R (Cirugía del Uruguay, 2020)
Based upon the study of a series of twenty six patinetns with pulmonary bulous emphysema physiopathology and therapeutic implications are comented.